An antimicrobial impregnated urinary catheter that reduces mineral encrustation and prevents colonisation by multi-drug resistant organisms for up to 12 weeks. (May 2019) - Belfield, Katherine; Chen, Xinyong; Smith, Emily F.; Ashraf, Waheed; Bayston, Roger
Graphical abstract: Abstract: Two major complications of indwelling urinary catheterisation include infection and mineral encrustation of the catheter. Our antimicrobial urinary catheter (AUC) impregnated with rifampicin, triclosan, and sparfloxacin has demonstrated long-term protective activity against major uropathogens. This study aimed to firstly assess the ability of the AUC to resist mineral encrustation in the presence and absence of bacteria. Secondly, it aimed to investigate the AUC's anti-biofilm activity against multi-drug resistant organisms. There was no difference in surface roughness between AUC and control segments. In a static and a perfusion model, phosphate deposition was significantly reduced on AUCs challenged with P. mirabilis . Furthermore, none of the AUCs blocked during the 28 day test period, unlike controls. The AUC prevented colonisation by methicillin-resistant Staphylococcus aureus, methicillin-resistant Staphylococcus epidermidis, extended-spectrum beta-lactamase producing E. coli, and carbapenemase-producing E. coli for 12 consecutive weekly challenges. All three drugs impregnated into the catheter continued to exert protective activity throughout 12 weeks of constant perfusion. The drugs appear to migrate into the crystalline biofilm to continually protect against bacteria not it direct contact with the catheter surface. In conclusion, the AUC reduces mineral encrustation and may increase time to blockage in the presence of P. mirabilis, and does not predispose to mineral deposition under other conditions. It also offers 12 weeks of protection against multi-drug resistant bacteria. Statement of significance: Infection and associated mineral encrustation of urinary catheters are two serious complications of indwelling urinary catheters. Others have attempted to address this through various technologies such as coatings, dips, and surface modifications to prevent infection and/or encrustation. However, all current 'anti-infective' urinary catheter technologies are limited to short-term use. Some patients with spinal injuries, multiple sclerosis, stroke survivors and others use long-term catheters for 4–12 weeks at a time with multiple catheterisation possibly throughout the rest of their life. We present a urinary catheter for long-term use that is impregnated with three antimicrobials by a patient-protected process to prevent infection and encrustation for up to 12 weeks, the maximum lifetime of a long-term catheter before it is changed.